Exploring closeness in parent-adolescent relationships (PAR) in a semi-rural, low-income community in the Western Cape Province of South Africa - Bomester, Olivia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.